News Writing for Television and Radio - Ricky W. Telg (EDIS)
Creating a television or radio story is more than hitting “record” on a video camera or audio recorder. You have to learn the process of writing an effective television and radio news story first. This 4-page fact sheet was written by Ricky Telg, and published by the UF Department of Agricultural Education and Communication, January 2015.